Contributos ao ensino de Óptica no ENADE à luz da Taxonomia de Bloom Revisada: Contributions to the teaching of Optics at ENADE in light of the revised Bloom’s Taxonomy - Araújo, Ana Clara Souza; Santos, Vitoria Hellen Juca dos; Romeu, Mairton Cavalcante (Revista Cocar, 2025)
Nesse escrito foram analisadas questões de Óptica presentes nas provas de Física das edições do ENADE. O objetivo deste artigo é conduzir investigações baseadas em critérios fundamentados na Taxonomia de Bloom Revisada, com o intuito de compreender o nível atual dessas variáveis. É uma pesquisa básica, quali-quantitativa e documental. Os resultados expressam que mesmo as questões de Óptica enfatizarem domínios superiores que vão além do simples memorizar, nenhuma delas alcançaram a dimensão metacognitiva do conhecimento, nem o domínio cognitivo mais alto “criar.” Tal observação nos leva a refletir sobre deficiências no ensino de Óptica em cursos superiores de Física. Além disso, pode-se atribuir também a formulação do próprio exame que não é fundamentado em níveis cognitivos e/ou taxonômicos. Palavras-chave: ENADE; Ensino; Óptica; Taxonomia de Bloom. Abstract This paper analyzes questions on Optics that are present in the Physics exams of the ENADE editions. The objective of this article is to conduct investigations based on criteria based on the Revised Bloom's Taxonomy, with the aim of understanding the current level of these variables. It is a basic, qualitative-quantitative research and documentary. The results express that even though the Optics questions emphasize higher domains that go beyond simple memorization, none of them reached the metacognitive dimension of knowledge, nor the highest cognitive domain “creating.” This observation leads us to reflect on deficiencies in the teaching of Optics in higher education Physics courses. In addition, it can also be attributed to the formulation of the exam itself, which is not based on cognitive and/or taxonomic levels. Keywords: ENADE; Teaching; Optics; Bloom's Taxonomy.